2020
DOI: 10.1002/jmv.25704
|View full text |Cite
|
Sign up to set email alerts
|

OPN is a promising serological biomarker for hepatocellular carcinoma diagnosis

Abstract: Hepatocellular carcinoma (HCC) accounts for 90% of cases of liver cancer and is one of the most common and lethal malignancies among all cancers. Current screening practices in high‐risk populations using ultrasound and serological α‐fetoprotein (AFP) have significantly reduced HCC mortality. However, considering the highly operative‐dependent nature of ultrasound and dissatisfactory diagnostic performance of AFP, there is an unfulfilled need for a biomarker that can be used in HCC‐related at‐risk population s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…OPN was also found to be able to detect preclinical tumors, that is, 87% of patients within 2 years preceding HCC diagnosis exhibited OPN levels above cutoff value ( 118 ). Similar results were found in another study (with AUROC of 0.851, sensitivity of 79.2%, and specificity of 80.5% for diagnosing HCC and AUROC of 0.838, sensitivity of 78.3%, and specificity of 79.6% for diagnosing ANHC) ( 83 ). A meta-analysis including 8 studies ( N = 1,399) found that serum/plasma OPN had a ability for predicting survival of HCC patients and an accuracy comparable to AFP for HCC diagnosis (the pooled sensitivity and specificity for OPN and AFP were 88 vs. 68% and 87 vs. 97%, respectively) ( 119 ); however, there is only one study to evaluate OPN for the diagnosis of early or AFP-negative HCC in this meta-analysis, so further assessment for the diagnostic value of plasma OPN in early and AFP-negative HCC is required.…”
Section: Blood Biomarkers For Anhc Diagnosissupporting
confidence: 88%
See 1 more Smart Citation
“…OPN was also found to be able to detect preclinical tumors, that is, 87% of patients within 2 years preceding HCC diagnosis exhibited OPN levels above cutoff value ( 118 ). Similar results were found in another study (with AUROC of 0.851, sensitivity of 79.2%, and specificity of 80.5% for diagnosing HCC and AUROC of 0.838, sensitivity of 78.3%, and specificity of 79.6% for diagnosing ANHC) ( 83 ). A meta-analysis including 8 studies ( N = 1,399) found that serum/plasma OPN had a ability for predicting survival of HCC patients and an accuracy comparable to AFP for HCC diagnosis (the pooled sensitivity and specificity for OPN and AFP were 88 vs. 68% and 87 vs. 97%, respectively) ( 119 ); however, there is only one study to evaluate OPN for the diagnosis of early or AFP-negative HCC in this meta-analysis, so further assessment for the diagnostic value of plasma OPN in early and AFP-negative HCC is required.…”
Section: Blood Biomarkers For Anhc Diagnosissupporting
confidence: 88%
“…DDK1 may also be a useful biomarker to predict the therapeutic response, as its serum levels dropped after surgery (81). However, other studies showed that plasma DKK1 levels may not be valuable for diagnosing ANHC (AUROC 0.551-0.620, sensitivity 54.4-89.1%, and specificity 37.9-61.5%) (82,83).…”
Section: Ddk1mentioning
confidence: 99%
“…54 These markers have been explored for the diagnosis of early stage HCC. The circulating proteins anti-Ku86, osteopontin, Dickkopf-1, and Golgi protein 73 have been shown to outperform the sensitivity of AFP for detecting early HCC 43,45,47,55,56 but no large trials have validated these results, and, to our knowledge, only osteopontin has been examined for detection of HCC prior to their detection by imaging. A pilot prospective study, including 22 Asian patients who developed HCC during follow-up, detected elevated osteopontin levels 12 months before diagnosis by imaging.…”
Section: Protein Biomarkers For Early Detection Of Hccmentioning
confidence: 99%
“…Serum samples from patients were obtained before any invasive procedure, such as surgery or biopsy, and before any nonsurgical oncologic treatment, such as chemotherapy or radiotherapy. The results showed significantly higher OPN values in patients with HCC (median 39.84 ng/ml, IQR=15.55-91.81) when compared with the values of patients with chronic hepatitis (median 10.18 ng/ml) and liver cirrhosis (10.93 ng/ml) (66). In the diagnosis of HCC in the risk group (patients with chronic hepatitis and liver cirrhosis) and AFP-negative individuals (with cut-off value of 20 ng/ml), OPN showed sensitivity of 78.26% and specificity of 80.45% (66).…”
Section: Phase 3 Osteopontine (Opn)mentioning
confidence: 88%
“…In HCC, the plasma levels of OPN have been considered as a potential biomarker (65). Zhu et al have conducted a study with 322 patients (105 with chronic hepatitis, 116 with cirrhosis and 101 with hepatocellular carcinoma) (66). Serum samples from patients were obtained before any invasive procedure, such as surgery or biopsy, and before any nonsurgical oncologic treatment, such as chemotherapy or radiotherapy.…”
Section: Phase 3 Osteopontine (Opn)mentioning
confidence: 99%